Samuel Beckett and Europe : history, culture, tradition - Bariselli, Michela; Bowe, Niamh M.; Davies, William, 1991- (Cambridge Scholars Publishing, 2017)
"Drawing on the diverse critical debates of the 'Beckett and Europe' conference held in Reading, UK, in 2015, this volume brings together a selection of essays to offer an international response to the central question of what 'Europe' might mean for our understandings of the work of Samuel Beckett. Ranging from historical and archival work to the close interrogation of language and form, from the influences of various national literary traditions on Beckett's writing to his influence on the work of other writers and thinkers, this book examines the question of Europe from multiple vantage points so as to reflect the ways in which Beckett's oeuvre both challenges and enlivens his status as a 'European writer'. With a full introductory chapter examining the challenging implications of the term 'Europe' in the contemporary period, this volume treats Europe as a recognition of the multiple ways that Beckett's poetry, criticism, prose and drama invite new understandings of the role of history, culture and tradition in one of the most significant bodies of writing of the twentieth century."--